STATISTICAL MODELLING OF THE OPINION AND PERCEPTION OF PEOPLE ABOUT DENGUE DISEASE (The Research of Medical Science Review, 2024)
The present research was conducted to know the opinion and perception of the people about the dengue disease. According to the opinion of the people, the best four factorscombinations was, indicated that covering water containers, cutting trees near houses,drying stagnant water and using mosquito nets were the important factors in preventing the dengue disease. A sample of 322respondents consisting of 222 case i.e. patients and 100 control. was collected from the three major hospitals of Peshawar. Out of 322 respondents, 186 nearly 58% were selected from the LRH, 94 participants were selected from KTH and 13% i.e. 42 were selected from HMC. Further out of 322 persons, 222 (698.94%) were dengue patients and 100 (31.06%) were healthy. Further 230 (71.43%) were illiterate and 92 (28.57%) were literate. Similarly, 56 (17.4%) respondents were below 25 years of age, 142 (44.1%) were below 35 years of age, 30.1% were below 45 years of age and 27(8.4%) respondents were above 45 years of age group. The analysis showed the association between the fever and gender, hospitals, age group, family income, education, marital status, knowledge about dengue virus, wearing complete dress. Further, Significant variables were the knowledge about the Use of mosquito net, Use of window net etc.